Avaliação da sanidade de Macacos-Prego-Galego (Sapajus flavius) mantidos em cativeiro no Estado da Paraíba - Ramalho, Ayodhya Cardoso (2014)
Marcgrave’s capuchin monkeys or blond capuchin monkeys (Sapajus flavius), Neotropical primate species newly discovered, are distributed in approximately 26 populations located in fragments of Atlantic Forest in the States of Alagoas, Pernambuco and Paraíba. These animals are classified as "critically endangered" and data on the health of these animals are scarce. The aim of this study was to evaluate the sanity of two populations of S. flavius kept in captivity in Paraíba. Research on the occurrence of hemoplasmas, with evaluation of hematologic and biochemical profiles, a survey of enterobacteria present in these two populations and investigate the occurrence of parasites was performed. Nine of 12 animals (75%) had infection 'Candidatus Mycoplasma haemomacaque ', despite the state of health of the animals did not indicate any disease. Regarding enterobacteria, we observed the presence of the genera Salmonella spp. in 87.5% (7/8), Shigella spp. in 12.5% (1/8) and Enterobacter spp. in 12.5% (1/8). Nematodes findings were identified as the species Dipetalonema gracile. Thus, we observe the importance of studies like these to learn more about the health aspects of these animals, helping in the development of management and conservation of this species in captivity projects aiming to release programs.